België verkoopt : de stille privatisering van de Belgische overheidsbedrijven - De Ruyter, Karin; Michielsen, Stefaan; Mortelmans, Johan (Groot-Bijgaarden : Scoop, 1994)
Bibliotheek François Vercammen
Nederlands
Monografie